2013
DOI: 10.1159/000346192
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Embryopathogenesis of VACTERL Association

Abstract: The nonrandom co-occurrence of vertebral, anorectal, cardiac, tracheoesophageal, genitourinary, and limb malformations, recognized as the VACTERL association, has not been satisfactorily explained from either a causation or embryopathogenesis standpoint. Few familial cases have been identified and maternal diabetes is the only environmental influence implicated to date. Mutations in single genes have been found in a number of syndromes with one or more of the VACTERL malformations, but these syndromes usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 122 publications
0
65
1
1
Order By: Relevance
“…The vertebrae develop early (23 to 32 days) in contrast to the formation of anorectal structures, which occur late in organogenesis (45 to 56 days). With this in mind several potential explanations need to be considered, as suggested by Stevenson and Hunter [36]: (1) teratogenic exposure throughout the entire organogenesis, (2) an inaugural malformation disturbing the development of other organs (malformation sequence), (3) disturbance of molecular pathways or single gene mutations involved in the formation of multiple organ systems, and (4) a general disturbance of the developmental process (for example vascular insufficiency). Most cases of VACTERL association are sporadic (~90%) [37] and high discordance rates in both monozygotic and dizygotic twin pairs have been reported [38] suggesting the impact of germline genetics to be minor in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The vertebrae develop early (23 to 32 days) in contrast to the formation of anorectal structures, which occur late in organogenesis (45 to 56 days). With this in mind several potential explanations need to be considered, as suggested by Stevenson and Hunter [36]: (1) teratogenic exposure throughout the entire organogenesis, (2) an inaugural malformation disturbing the development of other organs (malformation sequence), (3) disturbance of molecular pathways or single gene mutations involved in the formation of multiple organ systems, and (4) a general disturbance of the developmental process (for example vascular insufficiency). Most cases of VACTERL association are sporadic (~90%) [37] and high discordance rates in both monozygotic and dizygotic twin pairs have been reported [38] suggesting the impact of germline genetics to be minor in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the diabetic environment increases ROS production in these regions of the neural tube and in the primordia of the thoracolumbar (and posterior) paraxial mesoderm and neighboring intermediate and lateral plate mesenchyme (Stevenson and Hunter, 2013)-the primordia of the affected tissues listed above. As a result of cell stress and death, the expression of several genes responsible for the patterning and/or survival of these tissues including: HoxD13 (Garcia-Barcel o et al, 2008;Winberg et al, 2014), LPP (Arrington et al, 2010), and FoxF1 (Stankiewicz et al, 2009) associated with sonic hedgehog (Shh) signaling (Kim et al, 2001;Herion et al, 2014), Pcsk5 and GDF-11 (Szumska et al, 2008), FRANCB (Holden et al, 2006), and CHD7 (Winberg et al, 2014) may be reduced or absent.…”
Section: Diabetesmentioning
confidence: 99%
“…As a consequence of cell death, a number of developmental processes common to all VACTERL-affected organs, including the limb, could be disrupted (Mart ınez-Fr ıas et al, 1998;Bohring et al, 1999;Fr ıas et al, 2007;Stevenson and Hunter, 2013). The earliest potential process common to all the mesodermal organs affected in VACTREL is mesoderm production, resulting from migration of the epiblast through the primitive streak, distribution to sites of mesodermal precursors, and its subsequent proliferation (Mart ınez-Fr ıas et al, 1998;Bohring et al, 1999).…”
Section: Diabetesmentioning
confidence: 99%
“…To further assess the potential role of BAZ1A in the formation of human malformations, as seen in Case 2, we investigated the expression of Baz1a by whole-mount in situ hybridization (WISH) on mouse embryos at embryonic days (E) 10.5 to 13.5. This time frame represents the equivalent of human gestational weeks 5-8 hence, the postulated time of VATER/VACTERL organogenesis in humans (Stevenson & Hunter, 2013) (Figure 2). Strong expression of Baz1a could be detected in VATER/VACTERL associated tissues, such F IGUR E 1 Schematic representation of human ACF1 protein adopted from Zaghlool et al (2016).…”
Section: R Es Ult Smentioning
confidence: 99%